Eras of web mapping developments: Past, present and future - Veenendaal, Bert (2016)
Developments in web mapping and web based geographic information systems (GIS) have evolved rapidly over the past two decades. What began as online map images available to a small group of geospatial experts and professionals has developed to a comprehensive and interactive web map based on integrated information from multiple sources and manipulated by masses of users globally. This paper introduces a framework that outlines the eras of web mapping and significant developments among those eras. From this framework, some of the influences and trends can be determined, particularly those in relation to the development of technologies and their relation to the growth in the number and diversity of users and applications that utilise web mapping and geospatial information online.